Integration of e-Government Bases as a Means for Ensuring Economic (Tax) and Information Security - SEITOV, Bagdat T.; ZARKENOV, Medet S.; ZHEMPIISSOV, Nazarbek Sh.; KHUSSAINOV, Oleg B.; UTEPOV, Dauren P. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).38, 2020)
In this article, on the basis of an integrated approach, a comparative legal method of cognition, it is proposed to integrate the bases of electronic governments to improve measures to effectively counter economic crime and ensure economic security. Given the global progress in dynamically developing market and civil property relations, in the context of the digitalisation of the economy, the methods of committing many crimes are evolving, their qualitative characteristics and methods of commission are changing. According to the authors, the information model of the integration of electronic systems of tax and other state bodies into a single electronic system will successfully prevent and combat crimes in the field of IT-technologies at the initial stage of using information systems. In the future, the integration of electronic ‘Governments for citizens’ of different countries available for use by citizens and organisations in the field of taxes, public procurement, etc. into a single system will significantly increase information and economic security at the global level.